Systematic review and meta-analysis of randomized trials of central nervous system directed therapy for childhood acute lymphoblastic leukemia. - Richards, S; Pui, C; Gayon, P (2013)
Treatment of the central nervous system (CNS) is an essential therapy component for childhood acute lymphoblastic leukemia (ALL). Individual patient data from 47 trials addressing 16 CNS treatment comparisons were analyzed. Event-free survival (EFS) was similar for radiotherapy versus intrathecal (IT), and radiotherapy plus IT versus IV methotrexate (IV MTX) plus IT. Triple intrathecal therapy (TIT) gave similar EFS but poorer survival than intrathecal methotrexate (IT MTX), but additional IV MTX improved both outcomes. One trial resulted in similar EFS and survival with IV MTX plus IT MTX versus TIT alone. Radiotherapy can generally be replaced by IT therapy. TIT should be used with effective systemic therapy such as IV MTX.